Discontinuation of the renin–angiotensin system inhibitors improves erythropoiesis in patients with lower-risk myelodysplastic syndromes - Pavlidis, George (Ther Adv Hematol, 2021)
Renin–angiotensin system (RAS) blockade by angiotensin-converting enzyme inhibitors (ACEis) or angiotensin-receptor blockers (ARBs) has been related to anemia in various situations. We aimed to investigate whether discontinuation of RAS inhibitors improves erythropoiesis in patients with lower-risk myelodysplastic syndromes (LR-MDSs). Seventy-four patients with LR-MDS were divided into three groups matched for gender and age. Group A consisted of 20 hypertensive patients who discontinued RAS inhibitors and received alternative medications. Group B consisted of 26 patients who continued to receive ACEi/ARB and Group C included 28 patients (50% hypertensive) never exposed to ACEi/ARB. Half of the patients in each group were under treatment with recombinant human erythropoietin (rHuEPO). Data were collected at baseline and after 3, 6 and 12 months. Group A showed a significant increase in hemoglobin from 10.4 ± 1g/dL at baseline to 12.6 ± 1.2 g/dL after 12 months (p = 0.035) and in hematocrit (31.4 ± 3% versus 37.9 ± 4%, p = 0.002). Incident anemia decreased from 100% at baseline to 60% at 12 months (p = 0.043) despite a concomitant dose reduction in rHuEPO by 18% (p = 0.035). No changes in hemoglobin and hematocrit were observed in both Group B and Group C. In the subset of patients not treated with rHuEPO, improvement of erythropoiesis was found only in Group A, as measured by changes in hemoglobin (11.5 ± 1 g/dL versus 12.4 ± 1.3 g/dL, p = 0.041) and hematocrit (34.5 ± 3% versus 37.1 ± 4%, p = 0.038) after 12 months. In contrast, Group B and Group C decreased hemoglobin and hematocrit after 12 months (p < 0.05). In conclusion, discontinuation of ACEi/ARB in LR-MDS patients is followed by a significant recovery of erythropoiesis after 12 months.